Inculcation of Pancasila Ideological Values in Preventing Ideologically Motivated Criminal Acts of Terrorism - Budhiawan, Adlin; Lubis, Syaddan Dintara (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Instilling the ideological value of Pancasila to everyone has an inseparable importance in the life of the state. Pancasila is a value system that is extracted from the noble values of the Indonesian nation. These values have existed long before Indonesia's independence. It's just that now people's understanding of the ideological values of Pancasila is getting weaker in the life of the nation and state, this can be seen from the increasing issues of radicalism and terrorism that threaten the integrity of the state. The meaning of terrorism in Law Number 5 of 2018 is explicitly described that there is a motive/reason/cause of terrorism caused by the ideological motive behind the act of terrorism. Terrorism is implicitly described that there is a role of ideology as a motive for criminal acts of terrorism that cannot be underestimated. This paper tries to apply the approach in two analyses related to the problem under study. First, it tries to identify the extent to which Pancasila ideology has been instilled and reacted to the prevention of ideologically motivated terrorism crimes. Second, it tries to identify the extent to which the values of Pancasila ideology have been applied in the face of terrorism. The results found are the factors that cause the occurrence of ideologically motivated acts of terrorism in Indonesia due to the inability of a person to understand and apply the values of Pancasila ideology, especially the 1st, 2nd, and 3rd precepts comprehensively in life. The tendency to